1999
DOI: 10.1016/s0002-9440(10)65335-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Insulin-Like Growth Factor-1 (IGF-I) Receptor and the Invasiveness of Cultured Keloid Fibroblasts

Abstract: Keloid is a dermal fibroproliferative tissue of unknown etiology. Protein tyrosine kinases (PTKs) play an important role in the regulation of cell growth and differentiation. Activation of PTK cascades in keloid fibroblasts is thought to be closely linked to abnormal cell proliferation and migration. We determined the expression profile of PTK genes in normal skin and keloid fibroblasts using the homology cloning method with a degenerated primer. Eight PTK genes were expressed among a total of 46 receptor-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 28 publications
7
64
0
Order By: Relevance
“…Current findings (44,45) have demonstrated that the invasive activity of some cancer cells is largely dependent on IGF-IR. Because IGF-IR is thought to play a major role in growth and development of RCC, we here tested whether RCC can show IGF-IR dependent invasive activity.…”
Section: Inhibition Of Igf-i Signaling By Vhl Gene Product 20703mentioning
confidence: 97%
“…Current findings (44,45) have demonstrated that the invasive activity of some cancer cells is largely dependent on IGF-IR. Because IGF-IR is thought to play a major role in growth and development of RCC, we here tested whether RCC can show IGF-IR dependent invasive activity.…”
Section: Inhibition Of Igf-i Signaling By Vhl Gene Product 20703mentioning
confidence: 97%
“…Platelet-derived growth factor (PDGF)a receptor expression was shown to be enhanced in KFs, which corresponded to increased mitotic response upon exposure to all three PDGF isoforms (Haisa et al, 1994). Overexpression of insulinlike growth factor-I receptor detected in KFs appeared to enhance their invasiveness, but not fibroproliferation (Yoshimoto et al, 1999). Elevated interleukin (IL)-6 (Xue et al, 2000) and vascular endothelial growth factor (Wu et al, 2004) expression have also been observed in KFs.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies showed that cultured fibroblasts often exhibit characteristics typical of their in vivo phenotypes (Calderon et al, 1996;Tuan and Nichter, 1998;Yoshimoto et al, 1999;Younai et al, 1994). Although we described higher levels of caspase-2 and -3 expression in hypertrophic scars and keloid, Wassermann et al (1998) reported that the immunostaining levels of ICE and Fas were decreased in hypertrophic scar-derived fibroblasts.…”
Section: Akasaka Et Almentioning
confidence: 99%